(untitled) (Journal of Nepal Geological Society, 1985)
The river terraces and hill landforms have been surveyed in the· Siwalik mountains around Narayanghat in order to understand the nature of regional crustal movement. The river terraces are classified into six groups by airphoto interpretation and a field survey including soil color comparison. Deformation of terrace surfaces were found, and a past course of the Kali Gandaki has been identified to exist at an altitude of 170m high above the present river bed. Accordingly, the Siwalik Mountains in the area have upheaved since pre-Last Inter-glacial time.